Gut Microbiota: Novel Therapeutic Target of Ginsenosides for the Treatment of Obesity and Its Complications - Zhuang, Tongxi; Li, Wei; Yang, Li; Wang, Zhengtao; Ding, Lili; Zhou, Mingmei (Frontiers in Pharmacology, 2021)
Obesity, generally characterized by excessive lipid accumulation, is a metabolic threat worldwide due to its rapid growth in global prevalence. Ginsenosides are crucial components derived from natural plants that can confer metabolic benefits for obese patients. Considering the low bioavailability and degradable properties of ginsenosides in vivo, it should be admitted that the mechanism of ginsenosides on anti-obesity contribution is still obscure. Recently, studies have indicated that ginsenoside intervention has beneficial metabolic effects on obesity and its complications because it allows for the correction of gut microbiota dysbiosis and regulates the secretion of related endogenous metabolites. In this review, we summarize the role of gut microbiota in the pathogenetic process of obesity, and explore the mechanism of ginsenosides for ameliorating obesity, which can modulate the composition of gut microbiota by improving the metabolism of intestinal endogenous substances and alleviating the level of inflammation. Ginsenosides are expected to become a promising anti-obesity medical intervention in the foreseeable clinical settings.